Empathic Love Therapy untuk Menurunkan Pikiran dan Perilaku Self Injury - Tri Permatasari; Budi Andayani (Faculty of Psychology, Universitas Gadjah Mada, 2016)
Self injury is the act of deliberately inflicting harm on ones own body without suicidal intent.Prevalence of people with self injury is constantly increased each year especially in teenager and young adults. Empathic love therapy (ELT) is a method of love in psychosynthesis to reconcile every aspect in self, to change the destructive self pattern, and to find one’s true Self that in line with God’s will. The purpose of this study is to test the effectiveness of ELT in reducing self injury. There are 3 participants aged 20-30 years old which shows symptoms of self injury in the past year. This study use a single case design study. The measuring instrument are Daily Self Assessment (Diary) and Assessment of Empathic Love Therapy Sheets. Data analysis was performed by visual inspection and qualitative analysis. The finding of this study shows that ELT perform effectively in reducing self injury.